U.S. Coast Guard. Historian's Office collection - United States. Coast Guard. Historian's Office; Hughes, Riley; Morgan, William Ferguson; Smith, Ebenezer, active 1797-1840.
Autograph collection; account books of general merchant, Ebenezer Smith; draft, typescript, and galley proofs of Our Coast Guard Academy: A History and Guide by Riley Hughes, published in 1944; and miscellaneous papers. The autograph collection, compiled by William Ferguson Morgan, consists of the autographs of presidents James Buchanan, Grover A. Cleveland, Millard Fillmore, Ulysses S. Grant, Herbert Hoover, James Monroe, James K. Polk, and Martin Van Buren, and other leading figures in politics, business, the military, and the arts. Includes a letter dated 1846 from Henry Clay regarding the death of his son.
Library of Congress Prints and Photographs Division.
Collection material in English and Japanese.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Buchanan, James, -- 1791-1868 -- Autographs; Clay, Henry, -- 1777-1852 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Autographs; Fillmore, Millard, -- 1800-1874 -- Autographs; Grant, Ulysses S. -- 1822-1885 -- Autographs; Hoover, Herbert, -- 1874-1964 -- Autographs; Monroe, James, -- 1758-1831 -- Autographs; Polk, James K. -- 1795-1849 -- Autographs; Van Buren, Martin, -- 1782-1862 -- Autographs; Arts; Autographs; Businesspeople -- Autographs; Politicians -- United States -- Autographs; Presidents -- United States -- Autographs; United States -- Armed Forces